2021
DOI: 10.1111/jdi.13497
|View full text |Cite
|
Sign up to set email alerts
|

Glutamate is an essential mediator in glutamine‐amplified insulin secretion

Abstract: Aims/Introduction Glutamine is the most abundant amino acid in the circulation. In this study, we investigated cell signaling in the amplification of insulin secretion by glutamine. Materials and Methods Clonal pancreatic β‐cells MIN6‐K8, wild‐type B6 mouse islets, glutamate dehydrogenase (GDH) knockout clonal β‐cells (Glud1KOβCL), and glutamate‐oxaloacetate transaminase 1 (GOT1) knockout clonal β‐cells (Got1KOβCL) were studied. Insulin secretion from these cells and islets was examined under various condition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 42 publications
0
15
0
Order By: Relevance
“…Glutamate is produced via multiple transamination reactions including the BCAT‐dependent step of BCAA catabolism 42 . An increase in plasma glutamate may enhance insulin secretion since glutamate can serve as an insulin secretagogue via its conversion to α‐ketoglutarate by glutamate dehydrogenase 58,59 ; it is also a substrate for hepatic gluconeogenesis 60 . Stefan et al recently found that elevated plasma glutamate levels are associated with higher liver fat content, lower insulin sensitivity and increased carotid intima media thickness independent of total body fat mass and visceral fat mass 14 .…”
Section: Discussionmentioning
confidence: 99%
“…Glutamate is produced via multiple transamination reactions including the BCAT‐dependent step of BCAA catabolism 42 . An increase in plasma glutamate may enhance insulin secretion since glutamate can serve as an insulin secretagogue via its conversion to α‐ketoglutarate by glutamate dehydrogenase 58,59 ; it is also a substrate for hepatic gluconeogenesis 60 . Stefan et al recently found that elevated plasma glutamate levels are associated with higher liver fat content, lower insulin sensitivity and increased carotid intima media thickness independent of total body fat mass and visceral fat mass 14 .…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, glutamine provides precursors for GSH production, resulting in a decrease in the steady-state level of lipid oxidation products, a crucial component of cell viability [ 104 , 105 ]. In this context, glutamine availability is sensed by Glutaminase 1 (GLS1), which converts glutamine into glutamate for GSH synthesis and plays an important role in insulin secretion [ 106 , 107 , 108 , 109 ]. Notably, we discovered that endogenous GLS1 mRNA and protein expression were suppressed upon exposure to diabetic milieu conditions (hyperglycemia, streptozotocin, and H 2 O 2 ), leading to a reduction in GSH synthesis.…”
Section: Is Ferroptosis the Results Of Iron Accumulation And β-Cell D...mentioning
confidence: 99%
“…Interestingly, MIR125B-Tg islets displayed a 40% reduction on Imphd1 mRNA (padj 0.016) as well as lower levels of glutamine synthetase (GS, GLUL), a limiting enzyme for glutamine synthesis the inhibition of which reduced GSIS 46 . Of note, glutamine has been shown to strongly increase Ca 2+ influx in the presence of glucose, without changes in ATP content 47 .…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, MIR125B-Tg islets displayed a 40% reduction on Imphd1 mRNA (padj 0.016) as well as lower levels of glutamine synthetase (GS, GLUL ), a limiting enzyme for glutamine synthesis the inhibition of which reduced GSIS 46 . Of note, glutamine has been shown to strongly increase Ca 2+ influx in the presence of glucose, without changes in ATP content 47 . Secondly, decreased insulin secretion following KCl-mediated membrane depolarization in the absence of reduced intracellular Ca 2+ suggests the presence of functional voltage-dependent Ca 2+ channels in transgenic islets and points towards defects in the final steps of exocytosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation